Neutrophils enable local and non-invasive liposome delivery to inflamed skeletal muscle and ischemic heart - J,C; Najer,A; Blakney,A; McKay,P; Bellahcene,M; Winter,C; Sintou,A; Tang,J; Keane,TJ; Schneider,M; Shattock,R; Sattler,S; et al. (Advanced Materials, 2020)
Uncontrolled inflammation is a major pathological factor underlying a range of diseases including autoimmune conditions, cardiovascular disease, and cancer. Improving localized delivery of immunosuppressive drugs to inflamed tissue in a noninvasive manner offers significant promise to reduce severe side effects caused by systemic administration. Here, a neutrophilmediated delivery system able to transport drugloaded nanocarriers to inflamed tissue by exploiting the inherent ability of neutrophils to migrate to inflammatory tissue is reported. This hybrid system (neutrophils loaded with liposomes ex vivo) efficiently migrates in vitro following an inflammatory chemokine gradient. Furthermore, the triggered release of loaded liposomes and reuptake by target macrophages is studied. The migratory behavior of liposomeloaded neutrophils is confirmed in vivo by demonstrating the delivery of drugloaded liposomes to an inflamed skeletal muscle in mice. A single lowdose injection of the hybrid system locally reduces inflammatory cytokine levels. Biodistribution of liposomeloaded neutrophils in a humandiseaserelevant myocardial ischemia reperfusion injury mouse model after i.v. injection confirms the ability of injected neutrophils to carry loaded liposomes to inflammation sites. This strategy shows the potential of nanocarrierloaded neutrophils as a universal platform to deliver antiinflammatory drugs to promote tissue regeneration in inflammatory diseases.